Ghafur Ghulam's Stories Have Their Own Artistic Expression Characteristic of the Common Language Style - Nodira Hamidova (International Journal on Integrated Education, 2023)
In the article, Gafur Ghulam's stories reflect on the specific features of his artistic expression, characteristic of the style of the national language. The author proved that the writer was able to skillfully use the elements of the national language to give an artistic image based on individual colors and emotions with concrete details by researching the narrative text and its artistic expressions characteristic of the style of the national language.